Dermoscopic features and types of orf and milker’s nodule - Ayhan, Erhan; Aktaş, Hamza (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction: Orf and milker’s nodule are zoonotic cutaneous diseases generated by parapoxviruses. Contribution of dermoscopy to the diagnosis of these diseases has not been studied in the medical literature as to our knowledge. Aim: To investigate whether dermoscopy is a valuable diagnostic tool in orf and milker’s nodule diagnosis or not. Material and methods: In this study, macroscopic and dermoscopic features have been evaluated by including 46 lesions of 32 patients who have orf and milker’s nodule. Results: 56.5% (26) of lesions were orf, while 43.5% (20) of lesions were milker’s nodule (MN). Non-vascular dermoscopic structures have been determined as follows: blue-gray area (23.1% of orf, 35% of MN), orange-yellow streaks (19.2% of orf, 19.2% of MN), grayish-whitish streaks (26.9% of orf, 55% of MN), central yellow-white area (26.9% of orf, 35% of MN), crust (46.2% of orf, 40% of MN), erosion-ulceration (69.2% of orf, 55% of MN), yellow-white globule (11.5% of orf, 15% of MN), and yellow-white ring (57.7% of orf, 35% of MN). Limitations: Lack of PCR analysis, based of patient anamnesis types of orf and milker’s nodule. Conclusions: No significant dermoscopic differences have been determined between orf and milker’s nodule patients’ lesions. In our opinion, dermoscopy may be a useful tool to develop diagnosis of these diseases.